Facilities and Infrastructure to Support the Success of The Counseling Service Program Required in The Society 5.0 Era in Indonesian Schools - Zakki, Ahmad; S, Neviyarni; Firman, Firman; Amat, Muhammad Asyraf Bin Che (Jurnal Basicedu, 2023)
The era of Society 5.0 forces everyone to carry out their activities integrated with technology and information, including BK facilities and infrastructure. Several facilities and infrastructures need to be updated according to the development of the era because new needs arise. This research aims to find out and understand the changes in facilities and infrastructure needed in the Society 5.0 era to determine the success of counseling service programs in schools. This research is qualitative research with a naturalistic approach and data collection using document studies through literature studies, by reviewing books and journals that are by the object under study as primary data, with descriptive analysis techniques. The results obtained are the conditions of the facilities and infrastructure needed by BK to determine the creation of a successful program implementation. The efficiency of providing services to students is also influenced by the quality and novelty of BK facilities owned by schools. The technology and network available in the counseling room or things that can be accessed by counseling teachers and students will facilitate the implementation of counseling activities, resulting in more successful and productive activities with optimal results.